2000
DOI: 10.1002/(sici)1097-0274(200005)37:5<532::aid-ajim9>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Occupational exposure to chlorophenol and the risk of nasal and nasopharyngeal cancers among U.S. men aged 30 to 60

Abstract: Background Elevated rates of nasal and nasopharyngeal cancers have been associated with wood‐related occupational exposures, including chlorophenols, formaldehyde, and wood dust. Methods Occupational information was obtained from 43 nasal carcinoma cases, 92 nasopharyngeal carcinoma cases, and 1909 controls, by interview. Exact conditional logistic regression was used to evaluate the association of these cancers with chlorophenol exposure, estimated from a review of verbatim responses. Results Both nasal and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 25 publications
1
29
0
Order By: Relevance
“…A possible confounding effect of polychlorinated dibenzo-p-dioxins (see below), which occur as contaminants in chlorophenols, cannot be fully excluded. In humans, controlling for estimated formaldehyde and wood dust exposure did not alter the correlation between cancer and exposure, as much of the estimated chlorophenol exposure was among machinists (17). These findings support the hypothesis that occupational exposure to chlorophenol is a risk factor for nasal and nasopharyngeal cancer, although the role of machining-related exposures warrants further assessment (17).…”
Section: Polychlorophenolssupporting
confidence: 58%
See 1 more Smart Citation
“…A possible confounding effect of polychlorinated dibenzo-p-dioxins (see below), which occur as contaminants in chlorophenols, cannot be fully excluded. In humans, controlling for estimated formaldehyde and wood dust exposure did not alter the correlation between cancer and exposure, as much of the estimated chlorophenol exposure was among machinists (17). These findings support the hypothesis that occupational exposure to chlorophenol is a risk factor for nasal and nasopharyngeal cancer, although the role of machining-related exposures warrants further assessment (17).…”
Section: Polychlorophenolssupporting
confidence: 58%
“…Hence, their "analyses provide little evidence to support a relationship between the risk of childhood cancer and paternal occupational exposure to chlorophenate fungicides in British Columbian sawmills" (1). However, Mirabelli et al (17) did find an association between occupational exposure to chlorophenol and the risk of nasal and nasopharyngeal cancers in U.S. men 30-60 years of age.…”
mentioning
confidence: 96%
“…When the exposure over 40 years, for high exposure category the SRR was 20.98 (95%CI=16.04-27.46). Evidence of an excess of nasal and nasopharyngeal cancer had been observed in another study of chlorophenol and wood preservative exposed workers (Mirabelli et al, 2000). They obtained elevated risk for nasopharyngeal who held jobs assigned high intensity chlorophenol exposure (OR=9.07, 95%CI=1.41-42.9).…”
Section: 811 Historical Long-term Exposure To Pentachlorophenol and mentioning
confidence: 80%
“…Occupational exposure to fumes, smokes, dusts, or chemicals overall was associated with a 2-to 6-fold higher risk of NPC in some but not all studies (73,154,174,177,184). A few studies reported no association between solvents overall and risk of NPC (177,179,199,200), and other studies observed no associations with any occupational exposures examined (74,148,185). …”
Section: Risk Factorsmentioning
confidence: 94%
“…The majority of casecontrol studies examining cigarette smoking and risk of NPC in a variety of populations reported an increased risk of 2-to 6-fold (9,39,40,73,142,(172)(173)(174)(175)(176)(177)(178)(179)(180)(181), establishing tobacco smoke as a consensus risk factor for NPC (182), although some studies found no association (24,38,74,137,141,148,154,(183)(184)(185)(186). Reports of a positive association between domestic exposure to secondhand smoke and risk of NPC (40,146,180) are likewise countered by studies with null findings (39,174).…”
Section: Risk Factorsmentioning
confidence: 99%